Factors Affecting Audit Quality in Public Accounting Firms in Padang - ERFINES, Sherly; DAHEN, Lovelly Dwinda; ROSYA, Nilmadesri (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the influence of competence, independence, accountability, integrity, professionalism, and audit fees on audit quality in Public Accounting Firms (PAFs) in Padang City. This research employed a quantitative approach. Data were collected through questionnaires distributed to 37 auditors from 7 PAFs selected using purposive sampling. The data analysis techniques used in this study were descriptive analysis and inductive analysis employing multiple linear regression. The results show that competence, independence, integrity, and professionalism have a positive and significant effect on audit quality. Meanwhile, accountability and audit fees have no significant effect. Simultaneously, all six variables significantly influence audit quality, with an Adjusted R² value of 0.783, indicating that these variables can explain 78.3% of the variation in audit quality.